Early allogeneic immune modulation after establishment of donor hematopoietic cell-induced mixed chimerism in a nonhuman primate kidney transplant model - Little, Christopher J.; Kim, Steven C.; Fechner, John H.; Post, Jen; Coonen, Jennifer; Chlebeck, Peter; Winslow, Max; Kobuzi, Dennis; Strober, Samuel; Kaufman, Dixon B. (Frontiers in Immunology, 2024)
Background: Mixed lymphohematopoietic chimerism is a proven strategy for achieving operational transplant tolerance, though the underlying immunologic mechanisms are incompletely understood.: A post-transplant, non-myeloablative, tomotherapy-based total lymphoid (TLI) irradiation protocol combined with anti-thymocyte globulin and T cell co-stimulatory blockade (belatacept) induction was applied to a 3-5 MHC antigen mismatched rhesus macaque kidney and hematopoietic cell transplant model. Mechanistic investigations of early (60 days post-transplant) allogeneic immune modulation induced by mixed chimerism were conducted. Results: Chimeric animals demonstrated expansion of circulating and graft-infiltrating CD4+CD25+Foxp3+ regulatory T cells (Tregs), as well as increased differentiation of allo-protective CD-8+ T cell phenotypes compared to naïve and non-chimeric animals. In vitro mixed lymphocyte reaction (MLR) responses and donor-specific antibody production were suppressed in animals with mixed chimerism. PD-1 upregulation was observed among CD8+ T effector memory (CD28-CD95+) subsets in chimeric hosts only. PD-1 blockade in donor-specific functional assays augmented MLR and cytotoxic responses and was associated with increased intracellular granzyme B and extracellular IFN-γ production. Conclusions: These studies demonstrated that donor immune cell engraftment was associated with early immunomodulation via mechanisms of homeostatic expansion of Tregs and early PD-1 upregulation among CD8+ T effector memory cells. These responses may contribute to TLI-based mixed chimerism-induced allogenic tolerance.